Synthesis of 1-deoxy-1-hydroxymethyl- and 1-deoxy-1-epi-hydroxymethyl castanospermine as new potential immunomodulating agents - Vyavahare, Vinod P.; Chakraborty, Chaitali; Maity, Biswanath; Chattopadhyay, Subrata; Puranik, Vedavati G.; Dhavale, Dilip D. (Journal of Medicinal Chemsitry, 2007)
Two new C-1 epimeric hydroxymethyl castanospermine congeners 2a and 2b, synthesized by stereocon trolled intramolecular double reductive amination Of D-glucose derived beta-keto ester as a key step, showed impressive immuno-potentiating property. The bioactivity was mediated through up-regulation of T-H1/T-H2 cytokine ratio. The finding suggested that immunmodulatory activity of polyhydroxylated indolizidine alkaloids can be tuned by minor structural/stereochemical alterations.